OQİTİWDA KOGNITIV PEDAGOGIKALİQ TEXNOLOGIYALARDİŃ ORNİ HÁM ÁHMIYETI - Pazılov, M.A. (SCIENCE and SOCIETY, 2024)
This article will focus on the role and importance of cognitive pedagogy technologies in the educational process.